Ethnobotany for beginners - Albuquerque, Ulysses Paulino de (Springer Science and Business Media : Springer Nature, 2017)
Designed for new scholars, this book features a quick and easy-to-read discussion of ethnobotany along with its major developments. The language is clear and concise, objective and straightforward, and structured to lead the reader from the beginning of this science to the most recent developments. While there are some books on ethnobotany, mainly dealing with methods, this book covers the topic in an introductory and comprehensive text that prepares the reader for more advanced study of ethnobotany.
Keywords: Ethnobotany.; elektronické knihy; electronic books